2019
DOI: 10.1016/s2214-109x(19)30045-2
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and risk of cardiovascular disease in 20 low-income, middle-income, and high-income countries: the Prospective Urban Rural Epidemiologic (PURE) study

Abstract: Background Socioeconomic status is associated with differences in risk factors for cardiovascular disease incidence and outcomes, including mortality. However, it is unclear whether the associations between cardiovascular disease and common measures of socioeconomic status-wealth and education-differ among high-income, middle-income, and low-income countries, and, if so, why these differences exist. We explored the association between education and household wealth and cardiovascular disease and mortality to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
317
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(354 citation statements)
references
References 44 publications
28
317
2
7
Order By: Relevance
“…In the use of MR analysis, we found that longer EA was causally associated with the decreased odds of having cardiometabolic diseases, which is consistent with the traditional observational studies showing that socioeconomic status was associated with obesity, T2D, CVD, and even life expectancy (4,(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the use of MR analysis, we found that longer EA was causally associated with the decreased odds of having cardiometabolic diseases, which is consistent with the traditional observational studies showing that socioeconomic status was associated with obesity, T2D, CVD, and even life expectancy (4,(23)(24)(25)(26)(27).…”
Section: Discussionsupporting
confidence: 87%
“…Observational studies have consistently showed that socioeconomic status such as low education is associated with an increased risk of cardiovascular disease (CVD) and mortality (1)(2)(3)(4), but disentangling causality is challenging due to the long interval between exposure and outcome. Mendelian randomization (MR) analysis may help to clarify the relationship (5), which utilizes genetic variants as the unconfounded proxies for an exposure of interest and leverages the random assortment of alleles at the time of conception to overcome limitations inherent in observational studies, thus improving causal inferences.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have demonstrated income inequality in hospitalization, 20 not only in DM patients but also in the general population. 21,22 The present findings are consistent with those of previous studies. This study found that older male DM patients with medium and lowest incomes were at significantly greater risk of hospitalization for diabetic macrovascular complications than those at the highest income level.…”
Section: Results Of the Survival Analysis For Hospitalization And In-supporting
confidence: 94%
“…Tal fato é especialmente relevante se consideramos que marcadores socioeconômicos, tal como educação, podem influenciar os desfechos cardiovasculares independentemente dos fatores de risco convencionais. 22…”
Section: Discussionunclassified